The impact of socioeconomic conditions, social networks, and health on frail older people’s life satisfaction: a cross-sectional study - Helene Berglund; Henna Hasson; Katarina Wilhelmson; Anna Dunér; Synneve Dahlin-Ivanoff (Health Psychology Research, 2016)
It has been shown that frailty is associated with low levels of wellbeing and life satisfaction. Further exploration is needed, however, to better understand which components constitute life satisfaction for frail older people and how satisfaction is related to other life circumstances. The aim of this study was to examine relationships between frail older people’s life satisfaction and their socioeconomic conditions, social networks, and health-related conditions. A cross-sectional study was conducted (n=179). A logistic regression analysis was performed, including life satisfaction as the dependent variable and 12 items as independent variables. Four of the independent variables made statistically significant contributions: financial situation (OR 3.53), social contacts (OR 2.44), risk of depression (OR 2.26), and selfrated health (OR 2.79). This study demonstrates that financial situation, self-rated health conditions and social networks are important components for frail older people’s life satisfaction. Health and social care professionals and policy makers should consider this knowledge in the care and service for frail older people; and actions that benefit life satisfaction − such as social support − should be promoted.